Inherent Immune Cell Variation Within Colonic Segments Presents Challenges for Clinical Trial Design. (2nd April 2020) - Tyler, Christopher J; Guzman, Mauricio; Lundborg, Luke R; Yeasmin, Shaila; Perez-Jeldres, Tamara; Yarur, Andres; Behm, Brian; Dulai, Parambir S; Patel, Derek; Bamias, Giorgos; Rivera-Nieves, Jesús
Abstract: Background and Aims: Intestinal biopsy sampling during IBD trials represents a valuable adjunct strategy for understanding drug responses at the tissue level. Given the length and distinctive embryonic origins of the proximal and distal colon, we investigated whether inherent regional differences of immune cell composition could introduce confounders when sampling different disease stages, or pre/post drug administration. Here, we capitalise on novel mass cytometry technology to perform deep immunophenotyping of distinct healthy colonic segments, using the limited numbers of biopsies that can be harvested from patients. Methods: Biopsies [2.8 mm] were collected from the caecum, transverse colon, descending colon, and rectum of normal volunteers. Intestinal leukocytes were isolated, stained with a panel of 37 antibodies, and mass cytometry data acquired. Results: Site-specific patterns of leukocyte localisation were observed. The proximal colon featured increased CD8 + T cells [particularly resident memory], monocytes, and CD19 + B cells. Conversely, the distal colon and rectum tissues exhibited enrichment for CD4 + T cells and antibody-secreting cells. The transverse colon displayed increased abundance of both γδ T cells and NK cells. Subsets of leukocyte lineages also displayed gradients of expression along the colon length. Conclusions: Our results show an inherent regional immune cell variation within colonic segments, indicating that regional mucosal signatures must be considered when assessing disease stages or the prospective effects of trial drugs on leukocyte subsets. Precise protocols for intestinal sampling must be implemented to allow for the proper interpretation of potential differences observed within leukocyte lineages present in the colonic lamina propria.